(untitled) (Boca Raton, 1990)
Probably the most ubiquitous biochemical method used today for examining the genetics of individuals, populations, or phylogenetic relationships between taxa is electrophoresis. This book has been created to offer a viewpoint regarding current electrophoretic separation methodologies of macromolecules and their major applications to fisheries management. The chapters in this book have been selected and organized into three sections to create a carefully blended mixture of methodologies and applications designed to educate the novice, as well as stimulate interest in professional researchers currently using electrophoresis for their work.
Keywords: Electrophoresis,Fishery management,Quản lý nghề cá